"Pseudo PJRT"—Fast‐Slow AV Nodal Reentrant Tachycardia Presenting with Tachycardia‐Induced Cardiomyopathy. Issue 1 (2nd September 2011) - SELVARAJ, RAJA; ANANTHAKRISHNAPILLAI, AJITH; SADASIVAM, RAVISHANKAR; BALACHANDER, JAYARAMAN
<x xml:space="preserve">Abstract</x> A 52‐year‐old woman presented with left ventricular (LV) dysfunction and incessant narrow complex tachycardia. Electrocardiogram and clinical picture were suggestive of a permanent form of junctional reciprocating tachycardia, but electrophysiology study showed the tachycardia to be a fast‐slow form of atrioventricular nodal reentrant tachycardia (AVNRT). Slow pathway ablation terminated the tachycardia and the LV dysfunction resolved completely at follow‐up. Fast‐slow AVNRT has not been reported to present in incessant form, and the mechanism in this patient was absent retrograde fast pathway conduction resulting in easy initiation and maintenance of tachycardia. (PACE 2013; 36:e4–e6)